STUDY OF THE INFLUENCE OF OREGANO EXTRACT SUPPLEMENTATION IN WEANED PIGS OF THE EASTERN BALKAN BREED - N. Palova; G. Yordanova; R. Nedeva (Trakia Journal of Sciences)
An experiment with 30 weaned pigs of the East Balkan pig breed was conducted at the Agricultural Science Center in Sredets. The aim of the study was to determine the effect of oregano extract supplementation on the productivity and health status of weaned pigs of the East Balkan breed. The animals were divided into two groups of 15 animals, 8 males, and 7 females. The experiment started at 8,150 kg live weight for group I (control) and 8,160 kg for experimental group II. The animals from the control group received wheat: barley (50:50), and 50 g of oregano extract per 100 kg of feed was added to the ration of animals from experimental group II. The experiment finished at 19.646 kg live weight for group I and at 20.673 kg live weight for those in group II. The use of oregano extract (Origanum vulgare) in the feed for weaned pigs of the East Balkan breed improved the average daily gain (by 8.96%-0.146 kg vs. 0.134kg) and reduced the feed conversion ratio per kg gain by 8.22% (5.240kg vs. 5.709 kg).